Estimating a collective household model with survey data on financial satisfaction - Rob Alessie; Thomas F. Crossley; Vincent Hildebrand (Institute for Fiscal Studies (IFS), 2006)
We estimate a collective household model with survey data on financial satisfaction from the European Community Household Panel. Our estimates suggest that cohabitating individuals enjoy returns to scale in consumption that are towards the larger end of the range of estimates reported in the literature. They also suggest that the share of household income provided by the female partner is a significant determinant of her share of household consumption in most countries of the countries we study. – consumption ; returns to scale ; collective household models
Keywords: D12; D13; I31; 330